Unlocking interaction: A deep dive into metadiscourse in Indonesian and International EFL and ESL textbooks for Senior High School - Rismar Riansih; Angga Dwinka; Safnil Arsyad (UNIB Press, 2025)
This study presents a comparative corpus analysis of interactional metadiscourse features in two English textbooks used in Indonesian senior high schools: an EFL textbook published by the Indonesian Ministry of Education and Culture (Bahasa Inggris: Work in Progress) and an ESL textbook published by Cambridge University Press (English as a Second Language: Second Edition). Despite the central role textbooks play in shaping classroom discourse and developing students’ communicative competence, limited attention has been paid to how interactional metadiscourse is utilized in these materials, especially in EFL contexts like Indonesia, where textbooks often serve as the primary source of English input. Addressing this gap, the present study investigates how interactional metadiscourse, features that guide readers through the text and engage them, differ between a locally produced EFL textbook and an internationally published ESL textbook. The analysis was conducted using a corpus-based approach, drawing on Hyland’s (2005) model of interactional metadiscourse to manually identify and categorize features, including hedges, boosters, attitude markers, self-mentions, and engagement markers. The results revealed notable differences in the frequency and types of interactional metadiscourse employed in the two materials. These findings support the alternative hypothesis (H1), which posits that the international ESL textbook contains more interactional metadiscourse features than the Indonesian EFL textbook. The study contributes to the limited body of empirical research on metadiscourse in English textbooks and offers insights relevant to improving textbook design and English language instruction in the Indonesian context.